Developing a patient-driven chronic obstructive pulmonary disease (COPD) research agenda in the U.S. - Inga Gruß (SpringerOpen, 2021)
Plain English summary The COPD Patient-Powered Research Network (PPRN) asked adults with COPD and their caregivers to suggest areas for future research on COPD. Researchers analyzed 7336 survey responses and created six research areas to reflect their suggestions: (1) family/social/community research, (2) well-being, (3) research on a cure for COPD, (4) new drugs and treatments, (5) policy concerns, and (6) natural therapies. Several research topics patients and their caregivers identified as important have received little attention from researchers in the past and could be valuable topics for researchers to explore.